An open environment for development of manufacturing applications on vf-OS - Coutinho, C.; Lopes, L.; Viana, V.; Pape, D.; Klasen, G.; von Halem, B.; Garcia, O.; Stellingwerff, L.; Stam, A. (Enterprise interoperability: smart services and business impact of enterprise interoperability, 2018)
Innovative methodologies for development promote strong involvement of the development community and the developers' engagement. This chapter describes a novel environment that was envisioned for this purpose, involved in the scope of the H2020 European Project virtual factory Open Operating System (vf‐OS). The purpose of the H2020 vf‐OS European Project is to provide manufacturing businesses with an open Operating System that will allow them to create, develop, build and load applications that span and cover the whole manufacturing operation and process. The vf‐OAK software development kit (SDK) is a centralized environment for the development of applications and, generically, for centralized access to the vf‐OS assets and functionalities. The SDK for vApps has a process interpreter which can transform the results from the Process Designer tool to JavaScript language. The vf‐OS System Dashboard is a runtime, central dashboard and task manager, aimed at monitoring, warning, configuring, and adapting system resources.